Children and adolescents previously treated with glucocorticoids display lower verbal intellectual abilities. (23rd April 2015) - Holm, Sara Krøis; Vestergaard, Martin; Madsen, Kathrine Skak; Baaré, William F.C.; Hammer, Trine Bjørg; Born, Alfred Peter; Siebner, Hartwig R.; Paulson, Olaf B.; Uldall, Peter V.
Abstract Aim Perinatal exposure to glucocorticoids has been associated with adverse cerebral effects, but little is known about their effect on cognitive development and exposure later in childhood. This study examined intellectual abilities, memory and behavioural problems in children previously treated with glucocorticoids. Methods We evaluated 38 children aged from seven to 16 years, who had been treated with glucocorticoids for rheumatic disease or nephrotic syndrome, together with 42 healthy controls matched for age, gender and parental education. The median cumulative dose of prednisolone equivalents was 158 mg/kg (range 21–723) and the mean time that had elapsed since treatment was three‐and‐a‐half (standard deviation 2.2) years. Intellectual abilities were assessed with the Wechsler Intelligence Scale for Children and memory performance and behavioural problems with a pattern recognition memory task and the Child Behaviour Check List. Results There were no significant differences between the groups in pattern recognition memory, perceptual organisation index or behavioural problems, but patients had a significantly lower verbal comprehension index and this difference was present in both disease groups. There were no significant dose–response relationships regarding verbal intellectual abilities. Conclusion Children and adolescents previously treated with glucocorticoids seemed to have lower intellectual verbal abilities than healthy controls.